Evaluation of the performance characteristics of forced draft air-cooled heat exchangers and the effect of plume recirculation thereon - Conradie, Antonie Eduard (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng. (Mechanical)) -- University of Stellenbosch, 1991.